The effects of gender based violence on children: the case of Chikanga ward 14-Mutare - Mutenha, Amanda Chenai (Midlands State University, 2017)
The study focused on the effects of Gender Based Violence on children in Chikanga ward 14, a high density suburb in Mutare. The children have experienced the violence at home due to poverty, unemployment, infidelity and economic challenges among other causes. Twenty children from this area were identified as a sample of the study to have experienced the effects of violence directly or indirectly. All twenty of the children are of school going age between the ages of 10-18 years. The researcher used interviews and questionnaires as the data collection tools. The results are based on questionnaires and interviews directed to the children. The study found that Gender Based Violence has positive and negative effects on children. Due to Gender Based Violence some families have being legally disconnected from abusive relationships and because some are paying maintenance the children now have good education, good health facilities, good food and good shelter among many other basic necessities. Generally the children's standards of living have improved for the better. However, it is important to note that 80% of the respondents confirmed that Gender Based Violence has brought more evil compared to the good. The affected children highlighted issues like school drop outs, low self esteem, engaging into prostitution, crime, dropping grades in school, fear of the perpetrator, vulnerable to be abused by other people, looking up to other family units, attitude and behaviour bound to change and also early marriages to be the effects they experience due to Gender Based Violence. To survive these children beg, steal, do vending and also engage into piece jobs. Despite the few that have said to benefit from the Gender Based Violence it is a fundamental reality that cannot afford to be ignored that the larger number of children have been affected negatively by the viole